Estimation of Oxidative Stress and Some Trace Elements in Iraqi Men Patients with Type 2 Diabetes Mellitus - bijps; Abdulrahman R. Mahmood (College of Pharmacy University of Baghdad, 2017)
Type 2 diabetes mellitus (T2DM) is a chronic disorder that is associated with the imbalance of trace elements which are involved in many functions especially enzyme activities. Changes in the levels of serum elements probably can create some complications in type 2 diabetes mellitus.  Previous experimental and clinical studies report that oxidative stress plays a major role in the pathogenesis and development of (T2DM). However, the exact mechanism of oxidative stress could contribute to and accelerate the development of (T2DM). The aim of this study contained the following sections: firstly, to determine some biochemical parameters in subjects with type 2 diabetes mellitus (T2DM) like lipid peroxidation marker, malondialdehyde (MDA), total antioxidant capacity (TAC), and glycated haemoglobin (HbA1c). Secondly, to determine serum and urine levels of zinc as trace element and serum level of iron, then to compare those parameters with that for age matched healthy individuals. The study performed on 45 Iraqi men, who attended Baghdad Teaching Hospital. They were grouped into to 2 groups based on fasting serum glucose (FSG), and (HbA1c) value first group was included 20 healthful persons with A1c <6.4% as control non diabetic group, second group was included 25 patients with A1c>6.4% as T2DM. Outcomes of this study demonstrated a clear increase in T2DM in fasting serum glucose, ( HbA1c), MDA values, urine concentration of zinc , and serum level of iron compare to control.T2DM shows a significant reduction in both TAC and serum level of zinc ,if compared with control group .